Jahangir and the Jesuits : With an Account of the Travels of Benedict Goes and the Mission to Pegu - Guerreiro, Father Fernão (Brill | Manohar Publishers & Distributors, 2024)
A sequel to the volume, Akbar and the Jesuits , translated into English by C.H. Payne, in 1930, it describes the encounters of Jesuit missionaries in the Mughal court under Emperor Jahangir (r.1605-1627). The book is divided into three parts, the first part being the main theme of the book, which talks about the Jesuit account of court activities and their religious mission. The second part contains the accounts, which include the Travels of Benedict Goës and the third part is about the Jesuit mission to Pegu and the deputation of Portuguese emissaries to Goa. These parts discusses the first decades of the seventeenth century concerning the political happenings in the Mughal court and the Portuguese missions to South East and East Asia. The first part covers the infamous rebellion of Prince Salim against his father Emperor Akbar (r.1556-1605). It also covers the conversion of two Mughal princes to Christianity, the Jesuit father's mission to the Agra court, inter-faith debates between the Jesuit fathers and Muslim clergies, the Mughal king's reverence to Jesus Christ, and the neo-converts to the Christian faith. The second part of this book talks about Benedict Goës trip from Lahore, which was another Mughal capital, to Yarkand, situated in the current Xinjiang autonomous province of China, and Suchou in mainland China. The third part talks about the establishment of Portuguese rule in Burma with the Portuguese occupation of Pegu, discussing the conflicts between the Portuguese and Arakanese rulers and the establishment of Portuguese adventurer and mercenary Filipe de Brito e Nicote at Syriam.